2006
DOI: 10.1211/ijpp.14.3.0006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of medication adherence in hypertensive patients: an application of self-efficacy and the Theory of Planned Behaviour

Abstract: Objective The study aimed to identify the determinants of medication adherence in a population of hypertensive outpatients. The principle objective of the present study was to determine the utility of self‐efficacy and the Theory of Planned Behaviour (TPB) in predicting adherence with antihypertensive medication. Setting An outpatient hypertension clinic at the Belfast City Hospital, Northern Ireland. Method Outpatients who had attended the hypertension clinic on at least one previous occasion were invited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
4
27
2
1
Order By: Relevance
“…We also found that intention predicted the behaviour. Other studies have also observed similar findings (Bane et al, ; Chisholm et al, ). In Guénette's cross‐sectional study, intention was not related to noninsulin antidiabetic treatment adherence, only the perceived behavioural control (Guénette et al, ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We also found that intention predicted the behaviour. Other studies have also observed similar findings (Bane et al, ; Chisholm et al, ). In Guénette's cross‐sectional study, intention was not related to noninsulin antidiabetic treatment adherence, only the perceived behavioural control (Guénette et al, ).…”
Section: Discussionsupporting
confidence: 75%
“…In our study, it was observed that attitude and subjective norm, together, explained a significant portion of the variability of intention. Studies involving adherence to treatment regimens with other medications have also demonstrated the importance of attitude and subjective norm in the formation of intention (Bane, Hughes, & McElnay, ; Ben‐Natan & Noselozich, ; Chisholm, Williamson, Lance, & Mulloy, ; Rich et al, ). We also found that intention predicted the behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…factors related to patients' individual characteristics, [10][11][12] the social and economic resources available to them, 13,14 and their experiences of medical management, including appointments for evaluation or advice; enacting lifestyle changes and self-care; taking multiple medications; and living with therapeutic devices such as implantable cardioverter-defi brillators. 1 In other words, chronic heart failure is an illness that places a great deal of work on the patient.…”
Section: T R E At Men T Bur Den O F Chronic He a R T Fa Ilur Ementioning
confidence: 99%
“…There is growing interest in the concept of treatment burden internationally [1][4], and it has been hypothesized that treatment burden can overwhelm patients, exceeding their coping threshold and leading to poor adherence to therapies [7],[11],[12]. Coping thresholds are likely to vary substantially between patients, depending on environmental factors such as social support and financial constraints [5],[13],[14], and on internal factors such as health literacy and resilience [15],[16].…”
Section: Introductionmentioning
confidence: 99%